The Dynamic Correlation between Fiscal Spending on Education, Health, Consumption and Standard of Living in Nigeria - Ogbuagu, Anuli R.; Ewubare, Dennis B. (International Journal of Economics and Financial Issues, 2019)
The fiscal spending of the government have always been a strong instrument towards achieving development and recovering economy from recession. This paper investigates the long run and short run impact of three component of government expenditure (education, health, and consumption expenditure) on standard of living in Nigeria with time series data from 1981 to 2017. The study employs ordinary least square method of estimation on a range of equation models: Vector Error Correction Model (VECM) and the Impulse Responses Function Model. The result shows that fiscal spending on education, health, and consumption have a long run relationship with standard of living in Nigeria and the speed of adjustment towards long –run equilibrium is 61.45%, moderately high. The short run coefficient results reveals that education expenditure in both lag 1 &2 have a positive and significant impact on standard of living while health and consumption expenditure have insignificant impact on standard of living in Nigeria. Using Impulse Response Function model, we found that none of our fiscal spending variables (education expenditure, health and consumer spending) were able to emit positive impulses/shocks on the standard of living in Nigeria. The study recommends that government should ensure that fiscal spending on education, health, and consumption should be well managed, accounted for and the method should be transparent to the populace. Keywords: fiscal spending, education, health, consumption, standard of living JEL Classifications: E21, H51, H52 DOI: https://doi.org/10.32479/ijefi.8077